PENGARUH PROSEDUR PEMBERIAN KREDIT PEMILIKAN RUMAH SUBSIDI DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA REALISASI KREDIT DENGAN FASILITAS SUBSIDI BANTUAN UANG MUKA SEBAGAI VARIABEL INTERVENING - tommy munaf (STIE PEMBANGUNAN TANJUNGPINANG, 2020)
This study aims to determine empirically the influence of the procedures for granting credit and good corporate governance on the performance of credit realization by subsidizing down payment assistance as an intervening variable. This study uses a sample of 107 employees at Bank BTN Tanjungpinang Branch. The data obtained were analyzed using